Non-invasive measurement of tidal breathing lung mechanics using expiratory occlusion. Issue 2 (2020) - Howe, Sarah L.; März, Melanie; Krüger-Ziolek, Sabine; Laufer, Bernhard; Pretty, Chris; Shaw, Geoffery M.; Desaive, Thomas; Möller, Knut; Chase, J. Geoffery
Abstract: A great amount of research looks at whether information about lung mechanics can be obtained using spirometry, as these mechanics give clinically useful information about lung condition and disease progression. This study uses a time-varying elastance, single compartment lung model to calculate lung mechanics of 15 tidally breathing healthy subjects. A plethysmograph with a built-in shutter was used to induce an exponentially decaying airflow. Lung elastance and respiratory system resistance were separated from the decay rate of flow caused by the shutter. Occlusion resistance was calculated at shutter closure. To simulate upper airway obstruction, progressively larger resistances were added to the plethysmograph mouthpiece. Decay rates measured ranged from 5-42, with large intra-subject variation associated with muscular breathing effort. Measured lung elastance ranged from 3.9-21.2 cmH2 O/L and often remained constant as resistance was increased. Resistance calculated from the decay rate was very small, ranging from 0.15-1.95 cmH2 Os/L. The low resistance is due to the airflow measured originating from low resistance areas in the centre of airways. Occlusion resistance measurements were as expected for healthy subjects, and followed the expected resistance trend as resistance was increased.